Asynchronous Wind Turbine Generator: Output Power Evaluation - Nasr Ismael Alhusein (ITScience (Information Technology and Science), 2021)
In addition to photovoltaic (PV) power plants, wind turbine generators represent the most ubiquitous renewable energy use today. The stochastic and intermittent character of wind as a key source of electricity is one of the fundamental challenges associated with wind turbines WT. This paper describes an induction generator used in wind turbines. The implemented Turbine utilizes a straightforward output power against wind speed relationship to convert wind speed to turbine output power. When the wind speed is below or above the cut-in speed, the turbine produces no real power. Constantly, the machine consumes reactive power. This implemented block compensates for the machine's reactive power demand. Local load consumption is 75 kW. The electricity grid makes up for any shortage in wind turbine generation. When the generator's output exceeds 75 kW, the excess energy is exported to the grid.